THEORETICAL PRINCIPLES OF TRAINING SPECIALISTS FOR THE PRE-SCHOOL EDUCATION SYSTEM ON THE BASIS OF DUAL EDUCATION - qizi, Masharipova Barno Erkin (Journal of Learning on History and Social Sciences, 2024)
General Background: The training of specialists in the preschool education system is crucial for ensuring high-quality early childhood education, which significantly impacts children's development and learning outcomes. Specific Background: The dual education system, which combines theoretical learning with practical experience, has emerged as an effective approach for preparing educators. However, its application in preschool education remains underexplored, particularly in the context of engineering-pedagogy. Knowledge Gap: Despite the recognized benefits of dual education, there is a lack of comprehensive studies examining its theoretical principles and organizational frameworks within preschool education, leaving a gap in understanding how this approach can enhance the training of preschool educators. Aims: This article aims to elucidate the theoretical foundations and principles of training specialists for the preschool education system based on the dual education model, highlighting its relevance and effectiveness. Results: The findings suggest that the dual education system fosters a more integrated learning experience, enabling educators to apply theoretical knowledge in practical settings, thereby enhancing their pedagogical competencies. Novelty: This research introduces a conceptual framework for the dual education model specifically tailored for preschool education, emphasizing its unique contributions to developing skilled educators equipped to meet the diverse needs of young learners. Implications: The implications of this study advocate for the integration of dual education principles in preschool teacher training programs, encouraging educational institutions to adopt this model to improve training outcomes and ultimately enrich the quality of early childhood education.